Students' Perception On Duolingo in Enhancing Vocabulary Mastery - Nisrina Nisrina (Juliet, 2024)
The advent of technology has ushered in a plethora of engaging and innovative online learning tools for English, one of the them is Duolingo app standing out as an accessible and effective platform for language acquisition, particularly in English. This study aims to elucidate and observe students' perspectives on utilizing Duolingo software for vocabulary mastery at IAIN Lhokseumawe. Employing qualitative analysis techniques, the research employed a combination of tests, questionnaires, and interviews to gather data. The non-probability sampling method was utilized, with 20 students from the fifth semester selected as the sample. The study revealed that a majority of students were motivated to enhance their English vocabulary through the Duolingo application. The app provided an easy-to-understand platform, sparking interest and enthusiasm among students for learning new words. Furthermore, Duolingo proved the fact in preventing boredom during learning sessions and fostering novel approaches to learning. The research findings suggest a positive and highly beneficial perception among students regarding the use of Duolingo for enhancing vocabulary while learning English.